2019
DOI: 10.1016/j.foodchem.2018.07.181
|View full text |Cite
|
Sign up to set email alerts
|

Wheat (Triticum aestivum L.) flour free lipid fractions negatively impact the quality of sponge cake

Abstract: The functionality of wheat flour lipids in sponge cakes prepared from flour, sugar, eggs and leavening agents only was investigated by altering their location or content in flour. Hexane (hex) or the more polar hexane:isopropanol (3:2 v/v) (hex:isoprop) were used to impact free flour lipid (FFL) or both FFL and bound flour lipid (BFL) fractions, respectively. Flour from which the FFLs were removed resulted in significantly improved cake volumes and crumb structures. Additional removal of part of the BFLs did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 32 publications
6
42
0
Order By: Relevance
“…Foam‐type cake recipes mainly contain flour, sugar, and eggs. However, as shown in Table , many recipe variants exist (Çelik et al., ; Jarpa‐Parra et al., ; Oldham, McComber, & Cox, ; Pycarelle et al., ; Shepherd & Yoell, ). A major distinction is made between angel food and sponge cakes .…”
Section: Foam‐type Cake Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…Foam‐type cake recipes mainly contain flour, sugar, and eggs. However, as shown in Table , many recipe variants exist (Çelik et al., ; Jarpa‐Parra et al., ; Oldham, McComber, & Cox, ; Pycarelle et al., ; Shepherd & Yoell, ). A major distinction is made between angel food and sponge cakes .…”
Section: Foam‐type Cake Productionmentioning
confidence: 99%
“…This potentially negatively affects foam stability. In this context, Pycarelle et al (2019) have recently shown that free flour lipids, in particular, negatively impact cake volume and texture.…”
Section: Wheat Flourmentioning
confidence: 99%
See 2 more Smart Citations
“…sponge cake) or batter (e.g. pound cake) cakes (Wilderjans, Luyts, Brijs, & Delcour, 2013;Pycarelle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%